P036 Neutrophil extracellular traps in systemic lupus: a proteomic analysis. (21st February 2018) - Pratesi, F; Bruschi, M; Bonanni, A; Petretto, A; Puxeddu, I; Candiano, G; Ghiggeri, G; Migliorini, P
Abstract : Introduction: An altered formation and/or removal of neutrophil extracellular traps (NET) has been recently proposed as key event in systemic lupus (SLE): in fact, NETs have been detected in the skin and kidney of SLE patients, low density granulocytes from SLE patients form more frequently NETs and NET degradation is impaired. However, no data are yet available on NET composition in SLE patients. Objectives: The aim of the study is to compare NETs from SLE patients and normals by means of proteomic analysis. Methods: Neutrophils from 11 normals and 16 SLE patients (9/16 with active disease) were stimulated by PMA, NET proteins were released in supernatants by DNase treatment and characterised by Fusion Orbitrap Mass spectrometry. Results: Overall, 802 proteins were detected (50% identified in all the samples); 236 are exclusively found in control NETs, 57 only in active SLE and 22 in inactive SLE. Multidimensional scaling (MDS) showed that NETs composition/amount allows the identification of 3 different clusters corresponding to active SLE, inactive SLE and controls in a bi-dimensional scatter plot. The heat map describing the proteome profiles shows two different clusters of proteins, one represented by 16 proteins that were more expressed in inactive disease, the other by 9 proteins more expressed in active SLE. A preliminary analysis of posttranslational modifications showed a differential expression of methyloxidized and phosphorylated proteins. Conclusions: The data obtained suggest that NET composition and type/extent of posttranslational modifications are different in active SLE, in inactive disease and in controls. The different cytokine and autoantibody environment that distinguishes SLE flares from inactive may activate different pathways in NET induction and condition the quality and quantity of NET-associated proteins. Disclosure of interest: None declared